The group I pilin glycan affects type IVa pilus hydrophobicity and twitching motility in Pseudomonas aeruginosa 1244 - Allison, Tara M.; Conrad, Sean; Castric, Peter (Microbiology, 2015)
The group I pilin category is the most common type of type IVa pilus produced by Pseudomonas aeruginosa. The lateral surfaces of these pili are characterized by the presence of closely spaced, covalently attached O-antigen repeating units. The current work was conducted to investigate the pilin glycan's effect on pilus solubility and function. Culture supernatant fluids containing fully, partially and non-glycosylated P. aeruginosa group I pili were tested for solubility in the presence of ammonium sulfate. These results showed that while pili expressing three or four sugars were highly soluble under all conditions, those with fewer than three were insoluble under the lowest salt concentrations tested. A representative of the P. aeruginosa group II pili also showed low solubility when assayed under these same conditions. Reduced solubility suggested an increased pilus surface hydrophobicity, which was supported by protein modelling. While having no effect on the WT strain, an ionic strength found at many host infection sites inhibited surface and subsurface twitching motility of strain 1244G7, an isogenic mutant unable to glycosylate pilin. This effect was reversed by mutant complementation. Twitching motility of P. aeruginosa strain PA103, which produces group II pili, was also inhibited by ionic strengths which influenced the mutant 1244 strain. We suggest that the group I pilin glycan may, therefore, be beneficial to this organism specifically for optimal pilus functioning at the many host disease sites with ionic strengths comparable to those tested here.